Development of a patient-reported outcome measure in limb reconstruction: a pilot study assessing face validity. (1st September 2021) - Wright, Jonathan; Timms, Anna; Fugazzotto, Sharon; Goodier, David; Calder, Peter
Abstract : Aims: Patients undergoing limb reconstruction surgery often face a challenging and lengthy process to complete their treatment journey. The majority of existing outcome measures do not adequately capture the patient-reported outcomes relevant to this patient group in a single measure. Following a previous systematic review, the Stanmore Limb Reconstruction Score (SLRS) was designed with the intent to address this need for an effective instrument to measure patient-reported outcomes in limb reconstruction patients. We aim to assess the face validity of this score in a pilot study. Methods: The SLRS was designed following structured interviews with several groups including patients who have undergone limb reconstruction surgery, limb reconstruction surgeons, specialist nurses, and physiotherapists. This has subsequently undergone further adjustment for language and clarity. The score was then trialled on ten patients who had undergone limb reconstruction surgery, with subsequent structured questioning to understand the perceived suitability of the score. Results: Ten patients completed the score and the subsequent structured interview. Considering the tool as a whole, 100% of respondents felt the score to be comprehensible, relevant, and comprehensive regarding the areas that were important to a patient undergoing limb reconstruction surgery. For individual questions, on a five-point Likert scale, importance/relevance was reported as a mean of 4.78 (4.3 to 5.0), with ability to understand rated as 4.92 (4.7 to 5.0) suggesting high levels of relevance and comprehension. Flesch-Kincaid reading grade level was calculated as 5.2 (10 to 11 years old). Conclusion: The current SLRS has been shown to have acceptable scores from a patient sample regarding relevance, comprehensibility, and comprehensiveness. This suggests face validity, however further testing required and is ongoing in a larger cohort of patients to determine the reliability, responsiveness, precision, and criterion validity of the score in this patient group. Cite this article: Bone Jt Open  2021;2(9):705–709.